Responsibility of the Substitute Notary for Deeds Made Before the Notary's Leave - Maharani Azzara, Pasha; Widayati, Widayati (TABELLIUS: Journal of Law, 2025)
A notary is a public official authorized to create authentic deeds containing any legal actions, agreements, or provisions desired by the parties. In carrying out his/her duties, a notary has the right to take leave in accordance with statutory regulations. When taking leave, a notary must appoint a substitute notary to serve the public. The purpose of this study is to determine the status and authority of a substitute notary who receives a protocol from a notary taking leave and the form of legal responsibility of the substitute notary for the deeds he/she creates. The research method used in this study is normative law, which is conducted through the analysis of library materials or secondary data. This type of research is also known as research that focuses on the study of legal principles, legislation, and relevant legal literature. The research results show that a substitute notary has the same status and authority as a notary when carrying out his duties. The substitute notary also has full legal power over the deeds he makes, in accordance with applicable laws and regulations. Responsibility for notarial deeds occurs when the deed is signed and this falls under the authority of the official in office at the time of signing the deed. If the deed is made and signed before the notary's leave period, it will be the responsibility of the notary himself. Meanwhile, if the deed is signed after the notary has taken leave and the substitute notary has carried out his duties, it will be the responsibility of the substitute notary himself.